Penggunaan KIT IPA Sebagai Upaya Untuk Meningkatkan Hasil Belajar Konsep Energi Panas Di Kelas IV SD Negeri 1 Rumahtiga - Alberthina Abetsi Haumahu; Lamberthus Johannes Lokollo (Jurnal Pendidikan Geografi Unpatti, 2025)
his study investigates the effectiveness of using Integrated Science Kits (KIT IPA) in improving students' understanding of heat energy concepts in the 4th grade at SD Negeri 1 Rumahtiga. The study aims to improve student learning outcomes through an experiment-based learning approach that allows students to understand scientific concepts such as conduction, convection, and radiation in a more practical and applicable way. This research employs a classroom action research (CAR) approach, conducted in two cycles. The first cycle revealed challenges in student participation and understanding of the material, with 60% of students achieving the Minimum Mastery Criteria (KKM). However, after improvements were made in the second cycle, such as increased supervision, clearer explanations, and more interactive discussions, student learning outcomes showed significant improvement. By the end of cycle II, 80% of students had successfully achieved the KKM, indicating that the use of KIT IPA successfully enhanced student learning outcomes and engagement. The findings suggest that experiment-based learning using KIT IPA not only improves student test results but also strengthens their critical thinking skills, making it a valuable tool for teaching science at the elementary school level.